Yummy : the last days of a Southside shorty - Neri, Greg. (Lee & Low Books, 2010)
"A graphic novel based on the true story of Robert "Yummy" Sandifer, an eleven-year old African American gang member from Chicago who shot a young girl and was then shot by his own gang members"--Provided by publisher.